1974
DOI: 10.1063/1.1655398
|View full text |Cite
|
Sign up to set email alerts
|

Bremsstrahlung emission from laser - produced plasmas

Abstract: The x-ray bremsstrahlung from 4 to 50 keV emitted by laser-produced plasmas has been measured using a Bragg crystal spectrometer. Direct spectral information was obtained in contrast to earlier filter spectroscopy. Measurements were made with focal spot powers of 1016 W/cm2 of 1.06-μm radiation and 1014 W/cm2 of 10.6-μm radiation. A definite suprathermal electron component was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 4 publications
1
16
1
2
Order By: Relevance
“…A third explanation was offered for similar results ( Fig. 11-2 below) obtained in earlier work by Kephart et al 108 in terms of thermal flux inhibition (Sec. XI).…”
Section: B Suprathermal Electronssupporting
confidence: 58%
See 2 more Smart Citations
“…A third explanation was offered for similar results ( Fig. 11-2 below) obtained in earlier work by Kephart et al 108 in terms of thermal flux inhibition (Sec. XI).…”
Section: B Suprathermal Electronssupporting
confidence: 58%
“…These observations included electrons with energies greater than 50 keV, a large fraction of the laser energy appearing as fast ions, and less laser energy than expected being transmitted through thin foils. In related experiments, Kephart et al 108 reported x-ray spectra up to 50 keV, indicating a clear suprathermal electron component. A number of these observations were then modeled by Malone et al 591 They used a 1-D hydrodynamics code with a single electron temperature in which the heat flux was given by , except that f B was replaced by a much smaller number, f, now known as the "flux limiter."…”
Section: Thermal Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Une fraction de ces électrons très énergétiques (> 10 keV) pénètre dans la cible solide, induisant l'émission d'un rayonnement X. La partie énergétique du spectre de cette émission (X durs de 10 à 100 MeV) se présente sous la forme de raies caractéristiques dépendant du Z de la cible (Ka, Ko,...) et d'un fond continu (bremsstrahlung ou rayonnement de freinage) [2]. L'étude du rayonnement X dur obtenu lors d'une interaction laser-plasma a fait l'objet de nombreuses études dans plusieurs laboratoires.…”
Section: Introductionunclassified
“…L'étude du rayonnement X dur obtenu lors d'une interaction laser-plasma a fait l'objet de nombreuses études dans plusieurs laboratoires. Les premières expériences ont été réalisées avec de très grosses installations laser de puissance délivrant des impulsions laser relativement longues (nanoseconde) dans le domaine de l'infra-rouge [2][3][4][5][6][7][8][9]. Le développement de ces sources X pour l'imagerie médicale a été proposé très tôt [10].…”
Section: Introductionunclassified